The cinematic elements in the collection of Vasyl Symonenko "Silence and thunder" - Савчук, Григорій Олегович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article reveals the Intermedia aspects of the collection of V. Symonenko "Silence and thunder", in particular, the incorporation of cinematic elements. The relevance of the topic, its relationship with previous research are proven. The emphasis on the fact that in the sixties of the XX century in Ukraine the rapid development of all kinds of arts caused art diffusion. Poems that belong to the literary clips or contain their characteristics are analyzed: "Millstone", "Mower", "Lover", "Silence and thunder", "Oven". With the help of microanalysis, and the biographical method semantic structure of the poems, especially the clips, their role in the disclosure of the idea are disclosed. Particular attention is paid to the features of portraiture in the collection, portraits are shown in dynamics. The role of the eyes in the dynamic image is emphasized.  The cinematic elements in the intimate lyrics of the collection Silence and Thunder are considered.On the basis of observations on literary clips of V. Symonenko a number of conclusions are made. Mini-movies of collection based on peasant subjects at least for two reasons. First, the poet himself is a native of the village, and secondly, there is the influence of Soviet cinema about the village. Obviously, the author proves that the topic of the village can be a ground for broad generalizations. The cinematic material is most often the basis for the author's thoughts, so some of the poems of the book "Silence and thunder" resemble the structure of the fable. Using cinematic elements, the poet emotionally claims his stance, moralize, makes philosophical insights. Literature clips in the book combines the realistic and neo-romantic beginning. Neo-romantic intentions especially filled with footage that cannot be removed through the resources of traditional cinema, need animated effects.